Selective removal and recovery of gold and copper ions from aqueous solution by PKFAD-impregnated chitosan / Muhammad Ridhwan Abdul Rahim and Chang Siu Hua - Abdul Rahim, Muhammad Ridhwan; Chang, Siu Hua (2020)
Chitosan is one of the developing biosorbent that becomes main interest among the researchers since it can be used to recover various types of heavy metals in the aqueous solution. A lot of physical and chemical modification had been done toward the chitosan in order to increase its effectiveness for heavy metals recovery. This is because the conventional method like solvent extraction bring more negative impact to the environment In this research, the recovery of gold and copper ions from the aqueous solution has been investigated by using PKFAD-impregnated chitosan as biosorbent. The objectives are to investigate the effects of different parameters on the selective sorption of gold and copper from aqueous solution by PKFAD-impregnated chitosan and to propose suitable desorbing agents for gold and copper recovery from PKFAD-impregnated chitosan by literature review. To synthesis the PKFAD-Chitosan beads, it can be done through the impregnation method by which the viscous solution of chitosan is mixed with PKFAD. The investigated parameters for gold and copper ions recovery are pH of the aqueous solution, initial ratio concentration of aqueous solution and biosorbent dosage. Based on the result obtained, the highest percentage adsorption of Au(III) and Cu(II) can be achieved at pH = 3.24 (96.9%) and pH = 5.53 (71.1%) respectively. When the pH is increasing, the selectivity of Au(III) over Cu(II) reduced from 28.772 to 0.328. When the initial ratio concentration increasing, the adsorption capacity of gold increasing from 6.66 mg/g to 30.719 mg/g. However, the selectivity of Au(III)/Cu(II) is much lower compared to Cu(II)/Au(III) even though the concentration of Au(III) is five times higher than Cu(II). For the adsorbent dosage, the adsorption capacity were decreased for both Au(III) (13.29 mg/g to 3.94 mg/g) and Cu(II) (12.59 mg/g to 2.53 mg/g). The selectivity of gold over copper start to surpass at the adsorbent dosage 0.16 g. For the desorption process, the combination of eluents, thiourea and HCl is highly potential to recover Au(III) from PKFAD-Chitosan beads. Meanwhile, the recovery of copper can be done by using HCl, HNO3 and EDTA that act as the eluents.